1993
DOI: 10.1111/j.1476-5381.1993.tb13649.x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin receptors mediating contraction in goat cerebral arteries

Abstract: 1 The aim of the present study was to identify the subtype of receptor mediating contraction to endothelin-1 and sarafotoxin S6b in goat isolated middle cerebral arteries. 2 Endothelin-1, endothelin-2 and endothelin-3 contracted cerebral arteries in a concentration-dependent manner. Although the three peptides were full agonists, the order of potency was endothelin-1 = endothelin-2 > endothelin-3, with a relative potency of endothelin-1 and endothelin-2 versus endothelin-3 of -280. Sarafotoxin S6b induced conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…For example, we and others have previously demonstrated that BQ123 is a more potent inhibitor of S6b-mediated vascular responses than ET-1 (Bodelsson and Stjernquist, 1993;Maguire et al, 1996;Salom et al, 1993). Data from our present study provide evidence that the affinity of BQ123 as an antagonist of ET A -mediated β-arrestin recruitment was agonist-dependent, consistent with an allosteric mode of action of this compound [44] (Sokolowsky, 1993) whereas in the ET B assay BQ788 did not distinguish between the different agonists.…”
Section: Discussionsupporting
confidence: 88%
“…For example, we and others have previously demonstrated that BQ123 is a more potent inhibitor of S6b-mediated vascular responses than ET-1 (Bodelsson and Stjernquist, 1993;Maguire et al, 1996;Salom et al, 1993). Data from our present study provide evidence that the affinity of BQ123 as an antagonist of ET A -mediated β-arrestin recruitment was agonist-dependent, consistent with an allosteric mode of action of this compound [44] (Sokolowsky, 1993) whereas in the ET B assay BQ788 did not distinguish between the different agonists.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the inhibitory effect of BQ 123 on the ET-l-induced contraction seemed to be less than would have been anticipated for a pure ETA receptor-mediated response. Assuming a competitive inhibition at a single receptor population, the rightward shift of the ET-1 concentration-response curve produced by BQ 123 would yield a pKB value of 6.3, which is below the range of pA2 values (6.9-7.4) previously reported for vasoconstrictor responses claimed to be mediated by ETA receptors (Ihara et al 1992;Sumner et al 1992;Salom et al 1993;Feger et al 1994). This could indicate that ETB receptors also contribute to the endothelin-induced contractile responses in the rabbit basilar artery.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies of cerebral arteries from man (Adner et al 1994;Davenport et al 1995), goat (Salom et al 1993), rat (Feger et al 1994) and guinea-pig (Adner et al 1993) have indicated the presence of ETA receptors mediating vasoconstriction in these vessels. In the present study, the order of potency of the endothelins (ET-1 > ET-3) was in accordance with the properties of an ETA receptor (Masaki et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In preparations containing ET A receptors, for example, BQ‐123 is frequently more potent in inhibiting contractions induced by sarafotoxin S6b (StxS6b) and ET‐3, than similar responses to ET‐1. Such agonist‐dependent antagonist potency has been observed in rat aorta (Sumner et al , 1992), goat cerebral artery (Salom et al , 1993), human saphenous vein (Bax et al , 1993), human coronary artery (Godfraind, 1993), human umbilical artery (Bodelsson & Sjernquist, 1993) and human omental vein (Riezebos et al , 1994), as well as in rat vas deferens (Eglezos et al , 1993). These findings have prompted speculation concerning the possible existence of a population of BQ‐123‐insensitive ET A receptors (see Bax & Saxena, 1994 for review).…”
Section: Introductionmentioning
confidence: 83%